Characterization of chromosomal abnormalities in pregnancy losses reveals critical genes and loci for human early development. Issue 6 (29th March 2017) - Chen, Yiyun; Bartanus, Justin; Liang, Desheng; Zhu, Hongmin; Breman, Amy M; Smith, Janice L; Wang, Hua; Ren, Zhilin; Patel, Ankita; Stankiewicz, Pawel; Cram, David S; Cheung, Sau Wai; et al.
Abstract : Identification of critical genes for human early development within CNVs associated with pregnancy loss reveals the genomic clusters of developmental genes in the human genome. Abstract: Detailed characterization of chromosomal abnormalities, a common cause for congenital abnormalities and pregnancy loss, is critical for elucidating genes for human fetal development. Here, 2, 186 product‐of‐conception samples were tested for copy‐number variations (CNVs) at two clinical diagnostic centers using whole‐genome sequencing and high‐resolution chromosomal microarray analysis. We developed a new gene discovery approach to predict potential developmental genes and identified 275 candidate genes from CNVs detected from both datasets. Based on Mouse Genome Informatics (MGI) and Zebrafish model organism database (ZFIN), 75% of identified genes could lead to developmental defects when mutated. Genes involved in embryonic development, gene transcription, and regulation of biological processes were significantly enriched. Especially, transcription factors and gene families sharing specific protein domains predominated, which included known developmental genes such as HOX, NKX homeodomain genes, and helix‐loop‐helix containing HAND2, NEUROG2, and NEUROD1 as well as potential novel developmental genes. We observed that developmental genes were denser in certain chromosomal regions, enabling identification of 31 potential genomic loci with clustered genes associated with development.